Effects of contralaterally controlled neuromuscular electrical stimulation on the connectivity pattern of poststroke patients with hemiplegia - ZHU Lan; SUI Youxin; WANG Qinglei; XU Sheng; SHEN Ying; GUO Chuan (康复学报)
ObjectiveThe main purpose of this study was to apply functional near-infrared spectroscopy （fNIRS） to analyze contralaterally controlled neuromuscular electrical stimulation （CCNMES） related changes in functional connectivity （FC） within a cortical network after stroke.MethodsA total of 48 stroke patients with upper limb hemiplegia who were treated in the Rehabilitation Medical Center of Changzhou De'an Hospital were included in the study from July 2021 to January 2022. According to the computer-generated randomization list，they were divided into the control group and the observation group at a ratio of 1：1，with 24 cases in each group. The control group was treated with NMES，and two 4 cm×4 cm stimulating electrodes were placed on the extensor side of the affected forearm to produce wrist extension. The stimulation intensity was set at a level that could produce maximum wrist extension without causing discomfort to the patient，with a rectangular pulse of 60 Hz，a pulse width of 200 µs，and a stimulation period of 15 s on and 10s off. In the observation group，two 4 cm×4 cm surface electrodes and one reference electrode were placed on the extensor side of the healthy forearm，and two 4 cm×4 cm stimulating electrodes were placed on the extensor side of the affected forearm to generate wrist extension. The intensity of stimulation on the affected wrist was defined as the degree to which the affected wrist could be extended to the same extent （maximum elevation of the healthy wrist），but without causing pain. The other stimulation parameters were the same as those of the control group，and the stimulation duration was 10 min. In each task，The 35-channel fNIRS was used to measure the bilateral prefrontal cortex （PFC），primary motor cortex （M1） and primary somatosensory cortex （S1） in stroke patients. The differences in overall FC strength and mean FC strength based on ROI level between the two groups were analyzed.ResultsCompared with the NMES group，the overall connectivity strength of brain regions was higher in the CCNMES group，and CCNMES could enhance the functional connectivity between the affected M1 and the healthy M1 in patients with upper limb hemiparesis in stroke，as well as enhance the functional connectivity between the affected PFC and the healthy M1 and S1，respectively，and the difference was significant （P<0. 05）.ConclusionCCNMES triggers sensorimotor stimulation of the affected upper limb by active movement of the healthy upper limb and induces cortical functional reorganisation in stroke patients with hemiplegia.